A new Cretaceous terrestrial ecosystem from Gondwana with the description of a new sauropod dinosaur - Calvo,Jorge O. (2007)
A unique site at the northern area of Patagonia (Neuquén, Argentina) reveals a terrestrial ecosystem preserved in a detail never reported before in a Late Cretaceous deposit. An extraordinary diversity and abundance of fossils was found concentrated in a 0.5 m horizon in the same quarry, including a new titanosaur sauropod, Futalognkosaurus dukei n.gen., n.sp, which is the most complete giant dinosaur known so far. Several plant leaves, showing a predominance of angiosperms over gymnosperms that likely constituted the diet of F. dukei were found too. Other dinosaurs (sauropods, theropods, ornithopods), crocodylomorphs, pterosaurs, and fishes were also discovered, allowing a partial reconstruction of this Gondwanan continental ecosystem.